2016
DOI: 10.1139/cjas-2015-0139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water supplemented with Saccharicterpenin and photosynthetic bacteria on egg production, egg quality, serum immunoglobulins, and digestive enzyme activities of ducks

Abstract: Abstract:We investigated the effects of water supplemented with Saccharicterpenin and photosynthetic bacteria (PSB) on egg production, egg quality, serum immunoglobulins, and digestive enzyme activities of Jinyun ducks. A total of 400 healthy Jinyun ducks (all aged 58 wk) were randomly allotted to five treatments, with four replicates per treatment and 20 ducks in each replicate. The animals were fed a standard diet for 15 d and the experimental diet for 55 d. Experimental design is as follows: negative-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
(3 reference statements)
1
3
0
Order By: Relevance
“…In this study, the serum CAT activity was increased by saccharicterpenin. Similar results were obtained from the CAT activity of saponins in rats as reported by Liu et al. (2016) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the serum CAT activity was increased by saccharicterpenin. Similar results were obtained from the CAT activity of saponins in rats as reported by Liu et al. (2016) .…”
Section: Discussionsupporting
confidence: 90%
“…Saccharicterpenin is a new green additive derived from the extract of Theaceae plants as recognized by the Ministry of Agriculture of the People's Republic of China and is primarily composed of polysaccharides and triterpenoid saponins ( Liu et al., 2016 ). Saccharicterpenin exerts many functions, such as improving immunity ( Shen, 2010 , Zhang, 2010 ) and meat quality ( Huang, 2017 ), increasing digestive enzyme activity ( Liu et al., 2016 ), and enhancing intestinal development ( Huang et al., 2011 ) and growth ( Tang et al., 2007 , Fu et al., 2008 , Huang, 2017 ) in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the eggshell thickness and egg specific gravity significantly increased in treatment groups. Though the results were different from each other, there is evidence that exterior nutrition matter could change the material metabolism, and then alter egg quality (Olgun et al 2009;Liu et al 2016).…”
Section: Egg Qualitymentioning
confidence: 91%
“…However, in the current study, those prebiotics were not compatible with many of the LAB such as L. rhamosus and P. pentosaceus indicating the limited use of these commercial prebiotics in synergistic synbiotic application with these strains. Saccharicterpenin is a novel feed additive derived from extracts of Theaceae plants (Liu et al 2019 ) containing primarily polysaccharides and triterpinoides (Liu et al 2016 ) with wide variety of benefits to livestock including antioxidant activity (Liu et al 2019 ), intestinal development (Peng et al 2011 ), and digestive enzyme activity (Liu et al 2016 ). However, its prebiotic potential has not been studied to date.…”
Section: Discussionmentioning
confidence: 99%